PENGARUH DANA PIHAK KETIGA, LOAN TO DEPOSIT RATIO DAN RENTABILITAS TERHADAP KREDIT LPD KABUPATEN BADUNG - Dewi, Made Rusmala; Yadnya, I Putu; Sudiartha, Gede Mertha (E-Jurnal Manajemen, 2017)
Villace Credit Institutions (indonesia: Lembaga Perkreditan Desa or LPD) are saving and loan establishments owned by the members of the villages in Bali Province. They are economic means of the people of the villages. Activities of LPDs consist of accumulating societies’ funds in the form of savings and time deposits, providing loans to village members and accepting loans from various financial institutins. The aims of this research is to understand the significance of the impact of third parties’ funds, loan-to-deposit ratio (LDR), and rentability (return on asset, ROA) ratio on loans of LPDs in the Regency of Bandung, both simultaneously and partially. The sample of this research consists 55 LPDs, collected  under  purposive sampling method. Multiple linier regression is used in data analysis. Results indicate that simultaneously third parties’ funds, LDR, and ROA have significant effect on loans of LPDs in Badung Regency, with coefficient of determination (R2) of 0,901. Partially, third parties’ funds and ROA have positive and significant effect on loans of in Badung Regency. LDR has positive but insignificant effect on loans of LPDs in Badung Regency.